Student Reflections on PPL in The Application of Deep Learning, Character Education and Good Habitsin Elementary Schools: A Case Study - Feri Tirtoni; Amalia Qurrotul Ayun; Risma Inayatur Amaliyah; Risqina Mubarokah; Riswanda Apri Pramila (P3I UMSurabaya, 2025)
Character education and deep learning are important issues in the implementation of the Merdeka Curriculum in elementary schools. This study aims to explore the integration of deep learning, character education, and good habits in the Field Experience Practice (PPL) of students. A qualitative approach with a case study design was used in this study, involving interviews, observations, and document analysis as data collection techniques. The results of the study indicate that the integration of these three aspects contributes to the development of students' character, improves critical thinking skills, and strengthens moral and social values. Habits such as prayer and memorization, as well as extracurricular activities, play an important role in shaping students' character. This study contributes to the development of a more holistic character-based education curriculum that emphasizes not only academic achievement but also character building. Further research is recommended to explore quantitative measurements of this integration in a broader.